Newspeak − The Old Tool for New Purposes. How to use Newspeak Effectively in Order to Depreciate the “Enemy”? - Gwara, Ewelina Ewa (Emocje i polityka. Sceny z życia polskiego parlamentu, 2016)
The article aims to examine whether the language of contemporary politicians includes elements of newspeak, as well as what role the emotions play in the newspeak. The starting point of the analysis is a typology of characteristics of contemporary Newspeak created by M. Głowiński, that contains such a elements as: dichotomous view of the world, the idea of the enemy, conspiracy vision of the world. On the basis of typology by M. Głowiński, the article analyzes verbal and non-verbal behavior of three politicians: Jaroslaw Kaczynski, Janusz Palikot, and deceased founder of the political party Samoobrona (Self-defence), Andrzej Lepper.